Feeding habits of Leporinus friderici (Anostomidae: Teleostei) during a hydrobiological cycle in Vaupés River, Colombia - Velasco-Santamaría, Yohana María (2017)
The most important fish species of the Vaupes River is known as a Warakú tres puntos (Leporinus friderici), the most representative migratory Characidae from the Vaupés state, Colombia, with a significant importance in food security of indigenous communities. To contribute with the knowledge of its basic biology, we determined the habits and food preferences of Leporinus friderici, during one hydrobiological cycle (March 2014 to May 2015) in the Vaupés River, Colombia. Three sites were sampled, two of them along the Vaupés river (Yacayacá and Santa Cruz communities) and the other one in the Cuduyarí river, tributary of the Vaupés river (Piracemo community). Physical and chemical water parameters from the surface and depth level of the river were determined. Stomach contents from 316 fish were analyzed by frequency of occurrence (FO), gravimetric index, vacuity index (VI) and relative importance index (RII). Vaupés’s average depth in ascending water period was of 3.7 ± 0.6 m, during rainy season of 5.9 ± 1.4 m, in descending water period of 4.6 ± 1.3 m and during dry season of 2.4 ± 1.0 m. The higher acidity and turbidity were observed during the ascending water period. The average VI was 14.5 % for the period, but it reached 40 % in descending waters. In general, a FO of plant material was the most frequent (44.4-66.7 %), followed by insects (21.1-33.3 %, secondary diets). The gravimetric indices showed that plant material was the most consumed item, followed by insects, and in almost in equal proportion, invertebrates and animal material were observed. The differences in diet composition confirm the opportunistic nature of this species with a predominance of omnivorous habits. This study can be used as an integral part of the feeding ecology of L. friderici knowledge, in order to develop strategies for its protection in the Vaupés region because of its importance for local communities.